2002
DOI: 10.1124/dmd.30.9.997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexamethasone on Aryl (SULT1A1)- and Hydroxysteroid (SULT2A1)-Sulfotransferase Gene Expression in Primary Cultured Human Hepatocytes

Abstract: ABSTRACT:To determine whether the dexamethasone (DEX)-inducible hepatic sulfotransferase gene expression that has been described in the rat is conserved in humans, the effects of DEX treatment on hydroxysteroid sulfotransferase (SULT2A1) and aryl sulfotransferase (SULT1A1) gene expression were investigated in primary cultured human hepatocytes. Hepatocytes were prepared from nontransplantable human livers by collagenase perfusion of the left hepatic lobe, and cultured in Williams' medium E that was supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 35 publications
4
54
2
Order By: Relevance
“…These observations indicate that upregulation of cFLIP L -p43 by DEX is not associated with either the PI3K/Akt or NF-kB signaling pathways. Previous studies have shown that DEX can transcriptionally increase the expression levels of several genes in hepatocytes, such as sulfotransferase, 36 cytochrome P450 3A1, 37 connexin, 38 and multidrug-resistance protein 2. 39 Similarly, we here showed that increased cFLIP mRNA and protein levels by DEX treatment were markedly suppressed by the transcription inhibitor ActD, indicating that DEX increased cFLIP expression at the transcriptional step.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that upregulation of cFLIP L -p43 by DEX is not associated with either the PI3K/Akt or NF-kB signaling pathways. Previous studies have shown that DEX can transcriptionally increase the expression levels of several genes in hepatocytes, such as sulfotransferase, 36 cytochrome P450 3A1, 37 connexin, 38 and multidrug-resistance protein 2. 39 Similarly, we here showed that increased cFLIP mRNA and protein levels by DEX treatment were markedly suppressed by the transcription inhibitor ActD, indicating that DEX increased cFLIP expression at the transcriptional step.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have been known as important regulatory factors in the control of rat hepatic SULT2A enzyme activity (Fang et al, 2005a). The expression of rodent and human hepatic SULT2A is regulated by the Pregnane X Receptor (PXR) (Liu and Klaassen, 1996;Runge-Morris and Kocarek, 2005;Fang et al, 2005a;2005b;Duanmu et al, 2002). Dexamethasone administration produced significant increases in rat hepatic SULT2A mRNA and protein contents, relative to control (Fang et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone administration produced significant increases in rat hepatic SULT2A mRNA and protein contents, relative to control (Fang et al, 2005a). Treatment of human hepatocyte cultures with PXRactivating concentrations of dexamethasone and rifampicin both produced concentration-dependent increases in human SULT2A1 mRNA and protein contents (Fang et al, 2005a;2005b;Duanmu et al, 2002). In addition, more and more recent data suggest that hepatic SULT gene expression is regulated by the same transcription factor networks that also control the expression of the Cytochrome P450s (CYP), such as the Aryl hydrocarbon (Ah) receptor and members of the nuclear receptor superfamily, such as PXR, CAR and PPARα, although the co-regulation between the SULT and CYP gene families doesn't always occur in a coordinate direction (Runge-Morris, 1998;Runge-Morris and Kocarek, 2005;Jain et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This inducing effect is controlled, in part, by the bile acid-activated FXR (Song et al 2001). Similarly, human SULT2A1 has been shown to be induced in response to various ligands for the PXR (Kliewer et al 1998, Duanmu et al 2002, Echchgadda et al 2004). More recently, it has been determined that the CAR is also potentially involved in rodent SULT2A1 regulation (Saini et al 2004).…”
Section: Figurementioning
confidence: 99%
“…A number of studies reported single nucleotide polymorphisms (SNPs) within the human Sult2A1 gene (Igaz et al 2002), some of which have resulted in reduced levels of both enzyme activity and protein (Thomae et al 2002). Furthermore, research in both human and rodent SULT2A1 regulation has revealed that this gene may be controlled by various nuclear receptors including the constitutive androstane receptor (CAR) (Saini et al 2004), the pregnane X receptor (PXR) (Kliewer et al 1998, Duanmu et al 2002, Echchgadda et al 2004, and the farnesoid X receptor (FXR) (Makishima et al 1999, Song et al 2001. However, the involvement of nuclear receptors in the regulation of porcine SULT2A1 has not been determined.…”
mentioning
confidence: 99%